2009
DOI: 10.1371/journal.pntd.0000417
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regional Immune Response in Chagas Disease

Abstract: Following infection, lymphocytes expand exponentially and differentiate into effector cells to control infection and coordinate the multiple effector arms of the immune response. Soon after this expansion, the majority of antigen-specific lymphocytes die, thus keeping homeostasis, and a small pool of memory cells develops, providing long-term immunity to subsequent reinfection. The extent of infection and rate of pathogen clearance are thought to determine both the magnitude of cell expansion and the homeostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 82 publications
(109 reference statements)
4
65
0
6
Order By: Relevance
“…The protective immunity to T. cruzi infection appears to depend on the CD4 ϩ and CD8 ϩ T cell expressions of gamma interferon (IFN-␥) (98,330). A central role played by CD8 ϩ T cells in the control of T. cruzi infection in mice was suggested during the acute and chronic stages, when antigen-independent immunodominant memory T cells reach persistently high levels (102,302). Regulatory CD4 ϩ CD25 ϩ T cells have a limited role in infection by T. cruzi (340).…”
Section: Acquired Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…The protective immunity to T. cruzi infection appears to depend on the CD4 ϩ and CD8 ϩ T cell expressions of gamma interferon (IFN-␥) (98,330). A central role played by CD8 ϩ T cells in the control of T. cruzi infection in mice was suggested during the acute and chronic stages, when antigen-independent immunodominant memory T cells reach persistently high levels (102,302). Regulatory CD4 ϩ CD25 ϩ T cells have a limited role in infection by T. cruzi (340).…”
Section: Acquired Immunitymentioning
confidence: 99%
“…The challenge of mice with immunogenic recombinant calreticulin induces an inflammatory reaction against a host 45-kDa protein. It was suggested that calreticulin-induced inflammatory infiltrates foster autoimmunity in Chagas' heart disease (102,324).…”
Section: Autoimmunitymentioning
confidence: 99%
“…With an estimated total of 100 million people at risk of infection, about 8 to 10 million infected, and around 40,000 new cases per year, Chagas disease represents a major health, social, and economic problem in Latin America (1). The acute stage of infection is characterized by several transient abnormalities in the physiology of the immune system, leading to declines in cellular responses to mitogens, parasite antigens, or irrelevant antigens (2-4) that favor parasite colonization (5). These findings are consistent with reductions in the proliferation and expression of interleukin 2 (IL-2) and its high-affinity receptor IL-2R␣ (CD25) in murine T cells and human peripheral blood mononuclear cells (reviewed in reference 6).…”
mentioning
confidence: 99%
“…Así como en Chile no se dispone de BNZ, en diversos países no se usa NFX. Esto obedece a los efectos secundarios que ambos fármacos presentan y a diferencias de eficacia observadas, que probablemente están en relación a distintas cepas de Trypanosoma cruzi 20 . El NFX se ha demostrado más eficaz en Chile que en otros países de la región.…”
Section: Materials Y Métodounclassified